Performance of Column with Upper-Anchored Grouted Corrugated Duct Connections Under Load - Jie Zhang; Chenxi Fu; Yuanhong Fu; Siyuan Li (预应力技术)
The core goal of the prefabricated construction of urban prestressed concrete bridges is to improve structural performance and construction efficiency. To improve the construction convenience and load bearing performance of the connection between precast columns and pile caps, a novel connection structure for upper-anchored grouted corrugated ducts is proposed in this study. By comparing the pushover damage process of the integral casting column, the column connected by the grouting sleeve and the column connected by the upper-anchored grouted corrugated duct, the effects of the column height and the axial compression ratio on the performance of the column connected by the grouted corrugated duct were analyzed. Research results indicate that columns with upper-anchored grouted corrugated ducts exhibit superior static performance and ductility, with horizontal load-carrying capacities 23% greater than those of integrally cast columns and ductility performances 98% greater than those of integrally cast columns. Additionally, the primary concrete damage areas of these structures are farther from the bottom joint interface, featuring a wider distribution range of damaged areas and higher plastic hinge heights. When designing connections for columns with upper-anchored grouted corrugated ducts, controlling the elastic curvature ratio at section locations (sections with enlarged dimensions and sections at the base of columns) to be no less than 1.8 is recommended.